Effect of garment properties on air gap thickness and the contact area distribution. Issue 18 (November 2015) - Frackiewicz-Kaczmarek, Joanna; Psikuta, Agnes; Bueno, Marie-Ange; Rossi, René M
The heat and mass transfer in clothing is affected by the distribution of the air gap thickness and the contact area and this, in turn, results from the interaction between the geometrically complex shape of the human body, garment design, and fabric mechanical properties. In this study, the distribution of the air gap thickness and the contact area in typical shirts and undershirts were investigated using the three-dimensional scanning technique in relation to the garment style and fit, fabric properties, and body regions. This study showed that at the upper trunk the air gap thickness was unaffected by both the garment style and the fit, whereas the shape of the contact area was changed only by the fit. At the lower body the air gap thickness and the contact area changed proportionally with the increase of the ease allowances in the garments. As expected, larger air gaps were formed in shirts but larger contact areas were observed in undershirts. Consequently, results indicated the possibility of modeling the size of air layers in clothing by proper selection of the fabric type and ease allowances in clothing for a given body shape.